The proper use of forms in the diocesan Curia as an expression of the good formality of the ecclesiastical administration - CANOSA, JAVIER (Prawo Kanoniczne, 2018)
Canonical documentary formalities are also needed to guide the People of God well. These formalities safeguard important values that contribute to the vitality of the Church in so far as they are fair, timely and adequately carried out. It is necessary to make known the collections of forms but, above all, to convey that the well-used formality is of great help to the substantial goods of the Church.